Verificaciòn de concentraciòn de ion flúor en el agua y eliminaciòn en orina en niños con fluorosis severa de 7-15 años en el corregimiento juncal municipio de Palermo Huila (2019)
Dental fluorosis has become a public health problem in Colombia in recent years, an increase has been reported in some communities, water for human consumption contains high contents of fluoride ion, which is why they are at risk for dental fluorosis and others. alterations at a systemic level. In the urine analysis of the children of the town of El Juncal, high levels of fluorine ion were found. For this purpose, the water for human consumption was also analyzed, finding high levels of fluorine ion concentration in the water (exceeding 5ppm) for which It is believed that the main source of fluoride intake in this population is through water. Making a comparison with a population from Campoalegre, low levels of fluorine ion were found in urine (0.67ppm), while in water (1.05ppm) it was found within the limit recommended by the WHO for fluorine ion. The consequences of excessive intake of the fluoride ion is the accumulation in calcifying tissues such as teeth, which produces mottling in the tooth enamel. In other more severe cases, skeletal fluorosis and alterations of other organs are found that harm life. person's daily life.